Pengaruh Penambahan Kulit Jeruk Manis Dalam Berbagai Konsentrasi Dan Lama Fermentasi Terhadap Sifat Fisik Dan Kimia Nata De Citrus Dari Sari Buah Jeruk Manis (Citrus Sinensis) - sheva Matlubah; Nirmala Fitria Firdhausi; Hanik Faizah (Jurnal Agritechno, 2025)
Nata is a gel-shaped polysaccharide fermented by Acetobacter xylinum bacteria, with nata de coco as the most well-known product. The naming of nata is now adjusted to the media or fruit juice used, but the use of sweet orange juice and peel is still rarely done. This study aims to determine the effect of sweet orange peel concentration and fermentation time on the characteristics of nata from sweet orange juice. The method used is a Completely Randomized Design (CRD) and analyzed by ANOVA test. Treatment variations include sweet orange peel concentration (0.5%, 1%, and 1.5%) and fermentation time (10, 14, and 18 days). The parameters observed include physical and chemical properties. The results showed that the physical characteristics, namely the highest thickness and yield in sample E (1% sweet orange peel, 14 days fermentation) with values ​​of 2.17 mm and 18.72%, respectively. Meanwhile, the highest water content was found in sample G (0.5% sweet orange peel, 18 days fermentation) at 76.8%, and the highest cellulose content was recorded in sample J (positive control) at 3.066%.